Sodium selenite inhibits deoxynivalenol-induced injury in GPX1-knockdown porcine splenic lymphocytes in culture. Issue 1 (December 2018) - Ren, Zhihua; Fan, Yu; Zhang, Zhuo; Chen, Chaoxi; Chen, Changhao; Wang, Xuemei; Deng, Junliang; Peng, Guangneng; Hu, Yanchun; Cao, Suizhong; Yu, Shumin; Ma, Xiaoping; et al.
Abstract Deoxynivalenol (DON) is a cytotoxic mycotoxin that can cause cell damages. The main effect is to inhibit protein synthesis. Oxidative stress is one of the effects of DON. Selenium (Se) can ameliorate the cell damage caused by DON-induced oxidative stress, but it is unclear whether through selenoprotein glutathione peroxidase 1 (GPX1). We established GPX1-knockdown porcine spleen lymphocytes, and treated them with DON and Se. Untransfected porcine splenic lymphocytes (group P) and transfected cells (group M, GPX1 knockdown) were treated with or without DON (0.824, 0.412, 0.206, or 0.103 μg/mL, group D1-4), Se (Na2 SeO3, 2 μM, group Se), or both (group SD1–4) for 6, 12, or 24 h. The cells were collected and the activities of SOD and CAT, levels of GSH, H2 O2, malonaldehyde (MDA), total antioxidant capacity (T-AOC), and the inhibition of free hydroxyl radicals were determined. Levels of ROS were measured at 24 h. Compared with group P, the antioxidant capacity of group M was reduced. DON caused greater oxidative damage to the GPX1-knockdown porcine splenic lymphocytes than to the normal control cells. When Na2 SeO3 was combined with DON, it reduced the damage in the GPX1-knockdown porcine splenic lymphocytes, but less effectively than in the normal porcine splenic lymphocytes.